Changes in Smoking Behavior in the COVID-19 Pandemic: A Single Center Study in Family Practice - Mehmet Doğan; Hacı Ahmet Aydemir; Kamber Kaşali; Mustafa Bayraktar (Atatürk University, 2024)
Objective: There are controversial studies on smoking addiction in the COVID-19 pandemic. While some studies show increased tobacco use during the pandemic, others report increased smoking cessation attempts. This study examined changes in tobacco use and quit intentions during the COVID-19 pandemic compared to pre-pandemic.Methods: A cross-sectional study was designed and three groups were formed by including patients over 18 years of age, who were smokers, and who presented to the Education Family Health Center and had RT-PCR test results for COVID-19. Among these patients, patients with COVID-19 symptoms and complaints and positive RT-PCR test results constituted the COVID-19 positive group, patients who were COVID-19 negative but isolated due to their contacts constituted the contact group, and healthy people without any COVID-19 contact and symptoms constituted the healthy group. Demographic characteristics, smoking status before the COVID-19 pandemic, change in smoking status after COVID-19 test result or contact, and Fagerström nicotine dependence test results were compared.Results: Of the total 131 participants enrolled in the study, 70 were in the healthy group, 31 were in the COVID-19 negative group, and 30 were in the COVID-19 positive group. Men were predominant in three groups (60%, 83.9%, and 73.3% in normal, COVID-19-neg, and COVID-19-positive groups, respectively) with a small significant difference (p=0.048). The mean ages were 41.09±12.85, 38.21±11.69, and 39.47±11.66 years in the healthy, COVID-19 negative, and COVID-19 positive groups, respectively, with no significant difference (p>0.05). Fagerström dependence scores were 1.82±1.05, 1.53±0.86, and 1.40±0.72 in the healthy, COVID-19 negative, and COVID-19 positive groups, respectively, and were not statistically different (p>0.05). Smoking prevalence decreased by 1.13 (±4.17) cigarettes per day in the healthy group, by 3.97 (±5.31) cigarettes in the COVID negative group, and by 10.14 (±7.86) cigarettes in the COVID positive group, with a statistically significant decrease in smoking prevalence in all three groups (p